Forecasting volatility of the indian stock market - Khadilkar Guruprasad hari (Department of Rural Banking and Finance Management, College of Co-operation, Banking and Management, 2009)
The present study on ‘forecasting volatility of the Indian stock market’ was conducted with the main objectives of examining the volatility behaviour of the Indian stock market, to forecast the sector- wise volatility of the Indian stock market and to identify the most efficient volatility forecasting model among the different models used.